Metodologias analíticas para a caracterização química de amostra comercial do Óleo de Copaíba e atividade citotóxica sobre câncer gástrico (células AGS) - Lima, Lorena Souza (2022)
Copaifera is a genus of plant widely used in Brazilian folk medicine, among its many is the treatment of gastritis and stomach consultations. Typically, like this genus, which are used commercially as herbal medicines, they are chemically well peaked. This genus stands out for the presence of compounds such as sesquiterpenes and diterpenes. In this work, the use of techniques to identify these compounds will be demonstrated. Sesquiterpenes, being volatile, are easily identified by GC-MS. As it was possible to observe, the presence of the main sesquiterpenes already described, such as the main sesquiterpene β-caryophyllene (49.42%), and other sesquiterpenes such as trans-αbergamotene (16.22%), α-Copaene (4, 28%), γ-elemene (2.18%), and caryophyllene oxide (0.41%). As the sampled diterraneans of this genus are not observed by GC-MS, as they are also easy to demonstrate as a high chemical resolution for such analysis, this work is a fast methodology, based on the direct analysis of Mass Mass Spectrometry and Mass Fragmentation. in Multiple Stages (MSn), leads to the characterization of the main diterpenes, such as agatic acid, 3-hydroxycopalic acid, 3-acetoxycopalic acid, 3- hydroxylabdan-8(17)-en-15-oic acid, hardwickiic acid and chemical acid 7- acetoxyhardwicki allows to show the existence of substances not yet isolated by analitics methods of natural products. One sample also showed significant cytotoxic activity on gastric cancer cells (AGS cells, IC50 = 43.01 ± 0.7 μg/mL).